Systems Reliability Estimations of Models Using Exponentiated Exponential Distribution - Karam, Nada (Iraqi Journal of Science, 2024)
This article deals with estimations of system Reliability for one component, two and s-out-of-k stress-strength system models with non-identical component strengths which are subjected to a common stress, using Exponentiated Exponential distribution with common scale parameter. Based on simulation, comparison studies are made between the ML, PC and LS estimators of these system reliabilities when scale parameter is known.